Development and molecular cytogenetic characterization of alien introgressions conferring resistance to Hessian fly and Fusarium head blight in wheat - Cainong, Ronell Joey Carcallas (Kansas State University, 2014)
Hexaploid wheat (Triticum aestivum L., 2n=6x=42, AABBDD) is a recent polyploid and originates from a limited number of founder genotypes. Domestication bottlenecks further reduced genetic diversity. The wheat gene pool, which consists of landraces and wild relatives such as rye (Secale cereale L.), Leymus racemosus Tien and Elymus tsukushiensis Honda, is a rich source of genetic diversity. Agronomically important traits can be transferred from these gene pools to wheat through chromosome engineering. This dissertation describes chromosome engineering and pre-breeding efforts for resistance to Hessian fly and Fusarium head blight (FHB) in wheat. The germplasm with a whole-arm rye translocation, T2BS.2R#2L, contains the highly effective Hessian fly resistance gene, H21, and an unnamed powdery mildew resistance gene. Directed chromosome engineering was used to shorten the whole-arm rye segment. The recovered wheat-rye recombinant chromosome, T2BS.2BL-2R#2L, had a shorter rye segment but still contained the H21 gene and was transferred through backcrosses to adapted winter and spring wheat cultivars. This study released the germplasm KS09WGGRC51, which is used in wheat breeding programs in the U.S.A. Two novel sources of FHB resistance were identified in L. racemosus and E. tsukushiensis. Fhb3 present in the wheat-L. racemosus T7AL.7Lr#1S Robertsonian translocation was transferred into the adapted Kansas winter wheat cultivar Fuller. The wheat-E. tsukushiensis disomic addition translocation line confers FHB resistance. Ph1b-induced homoeologous recombination was used to produce wheat-E. tsukushiensis recombinants. The distal and interstitial recombinants were identified using molecular markers and genomic in situ hybridization (GISH). A combination of molecular cytogenetic analyses determined that the distal recombinant involved wheat chromosome 1A and a small distal segment originating from the E. tsukushiensis chromosome arm, 1E[superscript]ts#1S, resulting in the recombinant chromosome T1AL.1AS-1E[superscript]ts#1S. The interstitial recombinant involves an unidentified wheat chromosome and appears to be highly rearranged. Both recombinants confer high levels of type II FHB resistance (resistance to spread within the head) based on point inoculations in the greenhouse. To date, these two recombinants are the smallest alien introgression with FHB resistance in common wheat. This germplasm material has been released as KS14WGRC61. The distal recombinant can be used directly for breeding of FHB-resistant cultivars worldwide.
Keywords: Wheat germplasm improvement; Resistance; Molecular cytogenetics; Plant Pathology (0480)